The implementation of augmented reality-based flipbook learning media in improving vocational school students' critical thinking skills in the era of society 5.0 - Sabitri, Zenita; Rahayu, Sri; Meirawan, Danny (Universitas Negeri Padang, 2024)
In the era of Society 5.0, digitalization has changed the world of education and requires schools to develop creative, critical thinking skills. Vocational schools such as Vocational High Schools (SMK) play an important role in creating students who are ready to face the demands of this era. The use of learning technology, including media such as PowerPoint and modules, has become common but still needs innovation to reach the optimal level. Therefore, the implementation of virtual-based learning media is important. One of the innovations in learning media is the use of flipbooks with Augmented Reality (AR) in vocational schools. The main objective of this research is to measure the level of critical thinking skills of vocational school students. The results showed that the experimental class using Flipbook with AR achieved a significant increase in N-gain value (0.6), indicating the effectiveness of Flipbook with AR in improving students’ understanding. It can be seen from the average results of critical thinking aspects in the experimental class which has a percentage of 85%, while in the control class, it is 55%. Thus, this Flipbook with AR successfully improves students' ability in critical thinking aspects in SMK and shows great potential in the development of interactive learning technology for education.